Normative Contestation between Severance Pay and Employment Social Security in Indonesian Labour Law - Kurnia, Ade Chandra; Sesung, Rusdianto; Pratama, Febrian Rizki (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article analyzes the normative contestation between severance pay and employment social security benefits within Indonesian labour law following recent legislative reforms. The blurring distinction between employer-based severance obligations and contributory social security schemes has generated legal uncertainty, inconsistent judicial decisions, and potential erosion of worker protection principles in termination of employment cases.Purposes of the Research: The purpose of this research is to examine whether employment social security benefits, particularly Old-Age Security Benefits and Pension Security Benefits, may be lawfully interpreted as substitutes for or deductions from severance pay. The study aims to clarify doctrinal boundaries and reaffirm the protective function of labour law grounded in justice and employer responsibility.Methods of the Research: This research employs normative legal research using statutory, conceptual, and case approaches. Primary legal materials include labour legislation, constitutional provisions, and industrial relations court decisions, supported by scholarly literature. Legal interpretation and systematic analysis are applied to identify normative inconsistencies and formulate prescriptive legal conclusions.Findings of the Research: The findings reveal a fundamental normative misreading that conflates severance pay with employment social security benefits. This research offers originality by demonstrating that such substitution reallocates termination risk to workers, undermines legal certainty, and weakens labour protection. It proposes reaffirming severance pay as an independent, mandatory labour right.